Orthogonal Cysteine Protection Enables Homogeneous Multi‐Drug Antibody–Drug Conjugates. Issue 3 (14th December 2016) - Levengood, Matthew R.; Zhang, Xinqun; Hunter, Joshua H.; Emmerton, Kim K.; Miyamoto, Jamie B.; Lewis, Timothy S.; Senter, Peter D.
Abstract: A strategy for the preparation of homogeneous antibody–drug conjugates (ADCs) containing multiple payloads has been developed. This approach utilizes sequential unmasking of cysteine residues with orthogonal protection to enable site‐specific conjugation of each drug. In addition, because the approach utilizes conjugation to native antibody cysteine residues, it is widely applicable and enables high drug loading for improved ADC potency. To highlight the benefits of ADC dual drug delivery, this strategy was applied to the preparation of ADCs containing two classes of auristatin drug‐linkers that have differing physiochemical properties and exert complementary anti‐cancer activities. Dual‐auristatin ADCs imparted activity in cell line and xenograft models that are refractory to ADCs comprised of the individual auristatin components. This work presents a facile method for construction of potent dual‐drug ADCs and demonstrates how delivery of multiple cytotoxic warheads can lead to improved ADC activities. Lastly, we anticipate that the conditions utilized herein for orthogonal cysteine unmasking are not restricted to ADCs and can be broadly utilized for site‐specific protein modification. Abstract : Two is better than one : A general method for the preparation of homogeneous antibody–drug conjugates (ADCs) containing multiple payloads has been developed. This approach utilizes sequential unmasking of cysteine residues to enable site‐specific conjugation of each drug. Dual‐drug ADCs prepared through this approach had improved anticancer activities compared to single‐drug ADCs.